PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN BAHASA INDONESIA KELAS VIII.10 SMPN 2 SUNGGUMINASA - Nurwahidah; Elvira Sirenden (STKIP Subang, 2024)
This research is a Classroom Action Research which aims to increase students' learning motivation in the Indonesian language subject class VIII.10 SMPN 2 Sungguminasa. This research was carried out over two cycles with research procedures consisting of four stages, namely planning, implementation, observation and reflection. The research subjects were all 33 students in class VIII.10. Research data was obtained through observation and questionnaires. The data analysis technique used is descriptive qualitative. The research results show that the application of the culturally responsive teaching (CRT) approach can increase students' learning motivation in Indonesian language subjects as evidenced by an increase of 54.3% from 18.4% before the pre-cycle to 72.7% in the first cycle. an increase in Cycle I to Cycle II of 10.6% from 72.7% to 83.3%. Based on data analysis, it can be concluded that the application of the culturally responsive teaching (CRT) approach can increase students' learning motivation in Indonesian language subjects in class VIII.10 SMPN 2 Sungguminasa